2010
DOI: 10.1073/pnas.0910665107
|View full text |Cite
|
Sign up to set email alerts
|

Defining the ATM-mediated barrier to tumorigenesis in somatic mammary cells following ErbB2 activation

Abstract: p53, apoptosis, and senescence are frequently activated in preneoplastic lesions and are barriers to progression to malignancy. These barriers have been suggested to result from an ATM-mediated DNA damage response (DDR), which may follow oncogene-induced hyperproliferation and ensuing DNA replication stress. To elucidate the currently untested role of DDR in breast cancer initiation, we examined the effect of oncogene expression in several murine models of breast cancer. We did not observe a detectable DDR in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 59 publications
4
58
0
Order By: Relevance
“…However, in line with our conclusions with nude mice, it has been shown that senescent cells expressing an oncogenic form of HER2 are long lived in vivo, also in immunocompetent mice (28). Therefore, these reports also support that clearance of senescent cells in vivo depends on the oncogene that induced senescence, presumably because of the differences in senescence secretomes.…”
Section: Discussionsupporting
confidence: 80%
“…However, in line with our conclusions with nude mice, it has been shown that senescent cells expressing an oncogenic form of HER2 are long lived in vivo, also in immunocompetent mice (28). Therefore, these reports also support that clearance of senescent cells in vivo depends on the oncogene that induced senescence, presumably because of the differences in senescence secretomes.…”
Section: Discussionsupporting
confidence: 80%
“…In contrast to this robust activation of the DDR in BALBneuT-associated preneoplastic lesions, Reddy et al found that the DDR was either weak or absent in hyperplastic lesions arising in some other transgenic mouse models of breast cancer. For example, only modest induction of gH2AX was observed in mammary lesions from MMTV-ErbB2 transgenic animals (18). One possible explanation for this difference is that NeuT is more potently oncogenic than ErbB2 (11) and so is more likely to cause DDR activation.…”
Section: Discussionmentioning
confidence: 98%
“…As a consequence, HER2 promotes cell transformation 25,26 and elicits the constitutive activation of a panel of downstream signalling molecules including PI3K, SRC, AKT and MAPKs (reviewed in refs 23,24). Interestingly, it has been recently shown that ATM is phosphorylated on Ser1981 in a somatic mouse model of breast cancer dependent on the expression of HER2 (ERBB2/NeuN) receptor tyrosine kinase 27 . Although the functional significance of ATM phosphorylation (ATM-p) on Ser1981 in this context has not been fully elucidated 27 , the authors, given the identification of ATM phosphorylation on Ser1981 as a marker of ATM kinase activation in response to several stimuli 28 , propose that, in this context ATM is activated as part of the DDR to counteract tumour progression 27 as previously reported (reviewed in ref.…”
mentioning
confidence: 99%